Analysis of Lung Cancer Cases Presenting in Outpatient Department of University Hospital of Nepal - Karmacharya, R. M.; Singh, A. K.; Vaidya, S.; Tuladhar, S. M.; Devbhandari, M.; Lama, B.; Kharel, B. B.; Basnet, S. (Kathmandu University Medical Journal, 2022)
Background Lung cancer is one of the leading cause of cancer related death. Most common histopathology of lung cancer is non-small cell carcinoma of which adenocarcinoma is the most common. There are limited number of studies done in Nepal to know different aspects of lung cancer.Objective To know demographic parameters of patients diagnosed as lung cancer in a university hospital. The study also aims to know the different histopathological diagnosis of lung cancer.Method All the patients presenting to outpatient department (Cardio Thoracic and Vascular unit) of Dhulikhel Hospital, if are diagnosed as cancer of lung/bronchus will be included in the study. The duration of the study was January 2017 to December 2021. The details on age, gender, presenting symptoms, histopathology of lung cancer, operability will be included in database and will be analyzed.Result There were total of 127 patients diagnosed as lung cancer. Male:female ratio was 1.7:1. Overall mean age was 63.23 years (SD 13.5 years, Range 19-89 years). Non small cell carcinoma was the most common type of lung cancer with 83.7%. In non small cell carcinoma, most common type was Squamous cell carcinoma followed by undifferentiated and Adenocarcinoma. Only five (3.93%) cases were in operable stage.Conclusion Despite the fact that lung cancer is one of the most common cancer, patients usually present late and mostly are not in operable stage. This study shows that squamous cell carcinoma is the most common histopathology in lung cancer cases.